A Leakage-Inductance-Based ZVS Two-Inductor Boost Converter with Integrated Magnetics - Li, Q.; Wolfs, Peter (IEEE, 2005)
A two-inductor boost converter topology has conduction loss and transformer utilization advantages in converting low-voltage higher current inputs to high output voltages. In this letter, a new zero-voltage switching (ZVS) two-inductor boost converter with integrated magnetics is proposed. In the new topology, the two current source inductors, a resonant inductor and a two-winding transformer, are integrated into one single magnetic core with three windings. Two windings simultaneously perform the functions of the current source inductors and the transformer primary. The transformer leakage inductance forms the resonant inductance. This leads to a much more compact converter design with a significant reduction in the number of core and winding components. A theoretical analysis establishes the operating point of the ZVS converter. Both of the theoretical and experimental waveforms, including flux waveforms for the legs of the integrated core structure, are presented at the end of the letter.